Tourism development, energy consumption and Environmental Kuznets Curve: Trivariate analysis in the panel of developed and developing countries - Nanthakumar, Loganathan; Muhammad, Shahbaz; Khalid, Zaman (Elsevier Ltd, 2016)
The study investigates the relationship between economic growth, carbon dioxide emissions, tourism development, energy demand, domestic investment and health expenditures with an aim to test the validity of the Environmental Kuznets Curve (EKC) hypothesis in the panel of three diversified World's region including East Asia & Pacific, European Union and High income OECD and Non-OECD countries. The study covers the period of last nine years i.e. 2005–2013. The study used the principal component analysis (PCA) to construct tourism development index which is the amalgamation of number of tourists' arrivals, tourism receipts and international tourism expenditures. The results validate the inverted U-shaped relationship between carbon emissions and per capita income in the region. The results further substantiate the following causal relationships i.e. i) tourism-induced carbon emissions, ii) energy-induced emissions, iii) investment – induced emissions, iv) growth led tourism, v) investment led tourism and vi) health led tourism development in the region.